AGING AS A MODULATOR OF MULTIPLE SCLEROSIS PATHOPHYSIOLOGY - Đuretić, Jasmina (Srpski medicinski časopis Lekarske komore, 2026)
The number of older patients with multiple sclerosis is rising significantly, including individuals with late-onset disease (after age 50) and very late-onset disease (after age 60). Aging affects the immune and nervous systems, contributing to a shift in the clinical course towards a progressive pattern and increasing the risk of disease progression independent of relapse activity (PIRA). Additionally, late-onset multiple sclerosis is characterised by a more frequent progressive phenotype, fewer inflammatory relapses, and a shorter time to disability accumulation. Immune system aging (immunosenescence) leads to a reduced diversity of the T-cell receptor repertoire, changes in the number and function of CD4+ and CD8+ T lymphocytes, and an imbalance between effector and regulatory T cells. At the central nervous system level, aging contributes to neurodegeneration through increased oligodendrocyte degeneration, microglial dysfunction, iron accumulation, oxidative stress, mitochondrial dysfunction, and diminished neuroprotective mechanisms. Reduced proliferation and differentiation of neural stem cells, as well as structural and functional changes in glutamate receptors, primarily N-methyl-D-aspartate receptors, further compromise neuroprotective and reparative processes. Understanding the interactions between aging and the pathophysiological mechanisms of multiple sclerosis is crucial for developing targeted therapeutic strategies for the increasing population of older patients with multiple sclerosis. This paper aims to examine, through an integrative review of the available literature, the role of the aging process in modulating key pathophysiological mechanisms of multiple sclerosis.
Keywords: ageing; multiple sclerosis; immunosenescence; neurodegeneration